Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1029/2009jb006925
|View full text |Cite
|
Sign up to set email alerts
|

Rough faults, distributed weakening, and off‐fault deformation

Abstract: [1] We report systematic spatial variations in fault rocks along nonplanar strike-slip faults cross-cutting the Lake Edison Granodiorite, Sierra Nevada, California (Sierran wavy fault) and Lobbia outcrops of the Adamello Batholith in the Italian Alps (Lobbia wavy fault). In the case of the Sierran fault, pseudotachylyte formed at contractional fault bends, where it is found as thin (1-2 mm) fault-parallel veins. Epidote and chlorite developed in the same seismic context as the pseudotachylyte and are especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 64 publications
8
72
0
1
Order By: Relevance
“…The model does not account for numerous factors in the faulting process, including opening normal to the fault, nonuniform friction, displacement gradients, influence of fault tips, host rock anisotropy, selfaffine fault geometries, 3-D fault geometries, or pore fluid pressure variability [e.g., Dieterich and Smith, 2009;Griffith et al, 2010;Ritz and Pollard, 2012;Ritz et al, 2015]. As a result, it does not account for changes in elastic moduli in the damage zone resulting from accumulated inelastic deformation [e.g., Faulkner et al, 2006;Cappa et al, 2014;Xu et al, 2014].…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
See 2 more Smart Citations
“…The model does not account for numerous factors in the faulting process, including opening normal to the fault, nonuniform friction, displacement gradients, influence of fault tips, host rock anisotropy, selfaffine fault geometries, 3-D fault geometries, or pore fluid pressure variability [e.g., Dieterich and Smith, 2009;Griffith et al, 2010;Ritz and Pollard, 2012;Ritz et al, 2015]. As a result, it does not account for changes in elastic moduli in the damage zone resulting from accumulated inelastic deformation [e.g., Faulkner et al, 2006;Cappa et al, 2014;Xu et al, 2014].…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
“…Processes that cause damage zone growth include fault and process zone propagation and linkage [e.g., Cowie and Scholz, 1992;McGrath and Davison, 1995;Vermilye and Scholz, 1998], wear related to fault geometry [e.g., Scholz, 1987;Wilson et al, 2003], and off-fault plasticity accompanying earthquake rupture [e.g., Rice et al, 2005; J. P. Ampuero and X. Mao, Upper limit on damage zone thickness controlled by seismogenic depth, in Fault Zone Dynamic Processes: Evolution of Fault Properties During Seismic Rupture, AGU Monogr., edited by M. Y. Thomas, H. S. Bhat, and T. Mitchell, manuscripts in preparation, 2016]. Fracture modes and attitudes in the damage zone are a function of the stress field when they form, suggesting that fracture characteristics can be useful for constraining off-fault stresses [e.g., Kilsdonk and Fletcher, 1989;Saucier et al, 1992;Chester and Fletcher, 1997;Chester and Chester, 2000;Di Toro et al, 2005;Griffith et al, 2010]. Based on this relation, the types, distributions, and orientations of damage zone structures corresponding to each fault evolution process have been recognized in some cases, including mature faults that have experienced many slip events [e.g., Vermilye and Scholz, 1998;Wilson et al, 2003;Mitchell and Faulkner, 2009].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed decrease in average slip per stress drop due to fault roughness corresponds to a decreased frictional breakdown during sliding and thus a decrease in Δμ. Hence, fault roughness may be regarded as a bulk frictional agent [Griffith et al, 2010;Fang and Dunham, 2013], modifying the change in frictional resistance that is associated with a given stress drop (equation (5)). …”
Section: 1002/2016gl071700mentioning
confidence: 99%
“…Complementary image analysis allowed us to estimate both fracture density and 2D porosity (Fig. 1b) using fracture density analysis (Griffith et al 2010) and an open-source image processing software ImageJ. Fracture networks were traced in Illustrator and analyzed using MATLAB (Griffith et al 2010;Rempe et al 2014) to calculate fracture density, the results of which are shown in Table 1.…”
Section: Microstructural Analysis and Observationsmentioning
confidence: 99%